Software Defined Networks: Review and Architecture - Alam, Tanweer; Aljohani, Mohammed (Pandawan Sejahtera Indonesia, 2020)
In the fifth-generation communication system, secured and reliable data packets will rely on the network with high availability and low latency. The 5G network enables the dynamic control of nodes with low latency. Ultra-reliability is one of the challenging tasks in software-defined networks. The ultra-reliability feature is an interface working with high availability and low latency that brings in fifth-generation networks. The Internet of Things will work in the societies so that it required ultra-reliability features to empower the peoples as well as machines for collaborating with their neighbors. The connections among ultra-reliability networks are extremely hard situations to keep low packets corruption. The Software Defined Networks (SDN) will provide a platform for measuring, controlling, monitoring and scaling the smart objects in reality or virtually. Virtualization enables IT, specialists, to combine or separate the considerable networking or create new programmable networking among virtual machines. In this article, the authors are reviewed the architecture of SDN based on virtualization under the umbrella of 5G networks.